Factors Affecting Energy Efficiency and CO2 Reduction in The Manufacturing Firms of Thailand - Worawit Janchai; Anurak Panyanuwat (International Journal of Informatics and Information Systems, 2020)
Objective: The current study investigated the effects of management commitment, energy awareness, energy knowledge, energy audit towards energy efficiency which was further examined towards CO2 reduction in manufacturing firms of Thailand.Methodology: The sample of this study was gathered from manufacturing firms of Thailand and the sample size was 148 responses. The data was collected in a quantifiable manner and was analyzed using PLS-SEM.Findings: The paper should that energy audits have a positive and significant effect on energy efficiency. Energy awareness has a positive and significant effect on energy efficiency. Energy efficiency has a positive and significant effect on CO2 reduction. Energy knowledge has a positive and significant effect on energy efficiency. The management committee has a positive and significant effect on energy efficiency.Recommendations: Investing in human resource growth provides signs of determination to produce the desired results and, combined with administration encouragement and determination, the expected success can be achieved.